PENGEMBANGAN BAHAN AJAR E-MODUL PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN CANVA BERBASIS FLIPBOOK DI KELAS IV SEKOLAH DASAR - Syafra, Rafifatunnisa; Putera, Rafhi Febryan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the limited use of technology in developing teaching materials, despite schools having sufficient facilities. Teachers have not fully utilized these resources due to time constraints and a lack of skills in designing technology based materials. As a result, students often feel bored with monotonous learning content. This study aims to develop a valid, practical, and effective e-module for Civics Education using Canva in a flipbook format. The research is a development study (R&D) using the ADDIE model, which includes fives stages: Analyze, Design, Development, Implementation, and Evaluation. The e-module was validated by experts in content, language, and media. Its practically was assessed through questionnaires from teachers and students, and its effectiveness was evaluated based on student performance. The result showed that the e-module was valid, practical, and effective for learning. Validator feedback resulted in an overall score of 92.41%, categorized as “Very Valid”. Teacher response indicated practicality with scores of 94.28% at the trial school and 97.14% at the research school. Student responses showed scores of 92.76% at the trial school and 94.62% at the research school, both categorized as “Very Practical”. Effectiveness was proven by improved student learning outcomes at SDN 02 Talang Babungo and SDN 14 Talang Babungo after two learning sessions using the e-module. In conclusion, the Canva based flipbook e-module is valid, practical, and effective for use in grade IV elementary school classrooms.